OPTIMAL LOCATION SELECTION OF SOURCE SUBSTATION OF POWER DISTRIBUTION NETWORK - Ab Ghani, Mohd Ruddin (1999)
A new computer algorithm and program is presented in this paper for optimal location selection od source substation and optimal feeder selection in power distribution network. One of the objectives of power distribution system planning is to minimize the total cost of feeders of distribution system. Considering the cost of network and maintaining acceptable voltage of each feeder, a program is developed to select optimal location of the source substation. By using this solution technique an example of distribution network is solved which is presented in the paper.